The Old Story With a Difference : Pickwick's Vision - Wolfreys, Julian, 1958- (Book collections on Project MUSE., 2006)
The Old Story, with a Difference: Pickwick's Vision explores in radically different ways from most approaches to nineteenth-century studies the tropes and metaphors of vision in Dickens' first novel, The Pickwick Papers. The author provides a close reading of Dickens' Pickwick Papers and argues that this novel is an exemplary text for the re-consideration of concepts such as literature, history, the novel, and the whole notion of Victorian studies. True to the purpose of the Victorian Critical Interventions Series, Wolfreys challenges scholars to rethink the use of a canonical text in Victorian literature. --Back cover.